PqsE Is Essential for RhlR-Dependent Quorum Sensing Regulation in Pseudomonas aeruginosa - Marie-Christine Groleau (American Society for Microbiology, 2020)
ABSTRACT The bacterium Pseudomonas aeruginosa has emerged as a central threat in health care settings and can cause a large variety of infections. It expresses an arsenal of virulence factors and a diversity of survival functions, many of which are finely and tightly regulated by an intricate circuitry of three quorum sensing (QS) systems. The las system is considered at the top of the QS hierarchy and activates the rhl and pqs systems. It is composed of the LasR transcriptional regulator and the LasI autoinducer synthase, which produces 3-oxo-C12-homoserine lactone (3-oxo-C12-HSL), the ligand of LasR. RhlR is the transcriptional regulator for the rhl system and is associated with RhlI, which produces its cognate autoinducer C4-HSL. The third QS system is composed of the pqsABCDE operon and the MvfR (PqsR) regulator. PqsABCD synthetize 4-hydroxy-2-alkylquinolines (HAQs), which include ligands activating MvfR. PqsE is not required for HAQ production and instead is associated with the expression of genes controlled by the rhl system. While RhlR is often considered the main regulator of rhlI, we confirmed that LasR is in fact the principal regulator of C4-HSL production and that RhlR regulates rhlI and production of C4-HSL essentially only in the absence of LasR by using liquid chromatography-mass spectrometry quantifications and gene expression reporters. Investigating the expression of RhlR targets also clarified that activation of RhlR-dependent QS relies on PqsE, especially when LasR is not functional. This work positions RhlR as the key QS regulator and points to PqsE as an essential effector for full activation of this regulation. IMPORTANCE Pseudomonas aeruginosa is a versatile bacterium found in various environments. It can cause severe infections in immunocompromised patients and naturally resists many antibiotics. The World Health Organization listed it among the top priority pathogens for research and development of new antimicrobial compounds. Quorum sensing (QS) is a cell-cell communication mechanism, which is important for P. aeruginosa adaptation and pathogenesis. Here, we validate the central role of the PqsE protein in QS particularly by its impact on the regulator RhlR. This study challenges the traditional dogmas of QS regulation in P. aeruginosa and ties loose ends in our understanding of the traditional QS circuit by confirming RhlR to be the main QS regulator in P. aeruginosa. PqsE could represent an ideal target for the development of new control methods against the virulence of P. aeruginosa. This is especially important when considering that LasR-defective mutants frequently arise, e.g., in chronic infections.